2010
DOI: 10.1111/j.1365-2613.2010.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic pattern of skeletal muscle remodelling in different mouse strains

Abstract: Muscular injury associated with local inflammatory reaction frequently occurs in sports medicine, but the individual response and capacity of regeneration vary among subjects. Inflammatory cytokines are probably implicated in activation of repair mechanisms by specifically influencing tissue microenvironment. This work aimed to compare muscle tissue repair in different mouse lineages. We used C57BL/6 and BALB/c mice genetically predisposed to either Type1 or Type2 cytokine production. The role of Type1 cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Of note, our peritonitis experiments were conducted in C57BL/ 6J mice, with validation using a tissue-injury model and with pathway verification in human macrophages. In contrast, the previous study used BALB/c mice, which are more Th2-dominant, have different responses to both sterile and infectious insults, and demonstrate a less robust capacity to initiate tissue repair (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our peritonitis experiments were conducted in C57BL/ 6J mice, with validation using a tissue-injury model and with pathway verification in human macrophages. In contrast, the previous study used BALB/c mice, which are more Th2-dominant, have different responses to both sterile and infectious insults, and demonstrate a less robust capacity to initiate tissue repair (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 cytokine production (high IL-4) is altered in BALB/c tissues and results in delays in immune cell phagocytosis and muscle satellite cell activation 41 . We previously demonstrated that macrophages infiltrate both BL6 and BALB/c muscle tissue at a similar time after acute ischemia, however they persist longer in BALB/c muscle 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Next, rise in MMP expression and activity is associated with inflammation, including chronic inflammation observed in skeletal muscles of mdx dystrophic mice. [41][42][43][44] In this case regeneration of skeletal muscles affected by inflammatory process is disordered by the development of fibrosis. 25,26,43 In our experimental model, Soleus myolysis is rapid, extensive, and accompanied by massive inflammation.…”
Section: Discussionmentioning
confidence: 99%